Artykuł 41 Konstytucji Meksyku (brzmienie, objaśnienia, znaczenie) - Complak, Krystian (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The work deals with the key provision of the Mexico’s basic law concerning the electoral arrangements. Section 41 regulates the position and powers of political parties and two essential institutions playing a crucial role during general voting times, namely National Electoral Board (INE) and Electoral Tribunal of the Federation. This regulation is interesting from many points of view. It pertains to the so-called rambling, detailed sub-statute norms, widely exceeding matters regarded as constitutional. Its drafting commands to reflect not only on the correctness of law-shaping, but also about the future of this centennial constitution. Irrespective of these remarks, the commented rule shows the current level of evolving in that field of law in Mexico.
Keywords: constitutional acts drafting; today’s development of electoral institutions in Mexico; National Electoral Board (INE); Electoral Tribunal of the Federation; general elections in Mexico